Reimbursement or compensation for damages caused by war: the civil law aspect - M. О. Parii (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to the study of the correlation between the concepts of reimbursement and compensation for damages, including during the war. The author highlights the issue of distinguishing between the concepts of reimbursement and compensation as synonymous categories. It is determined that the term “compensation” is broader in scope and includes the narrower term “reimbursement”, as well as additional features – remuneration or payments. It is proposed to change the use of the established phrase “reimbursement of moral damage” to “compensation for moral damage” due to the impossibility of accurate determination of the amount of reimbursement due to the non-property component and the need to compensate a person for a certain amount of compensation for suffering, especially in wartime.